1998
DOI: 10.1016/s0925-4439(98)00015-5
|View full text |Cite
|
Sign up to set email alerts
|

Proton NMR spectroscopic analysis of multiple acyl-CoA dehydrogenase deficiency—capacity of the choline oxidation pathway for methylation in vivo

Abstract: Proton NMR spectra of urine from subjects with multiple acyl-CoA dehydrogenase deficiency, caused by defects in either the electron transport flavoprotein or electron transport flavoprotein ubiquinone oxidoreductase, provide a characteristic and possibly diagnostic metabolite profile. The detection of dimethylglycine and sarcosine, intermediates in the oxidative degradation of choline, should discriminate between multiple acyl-CoA dehydrogenase deficiency and related disorders involving fatty acid oxidation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…In one other patient in whom riboflavin therapy was started during severe metabolic decompensation fatal outcome could not be prevented [[16]]. Only one patient was reported to be clearly unresponsive to riboflavin [[17]].…”
Section: Resultsmentioning
confidence: 99%
“…In one other patient in whom riboflavin therapy was started during severe metabolic decompensation fatal outcome could not be prevented [[16]]. Only one patient was reported to be clearly unresponsive to riboflavin [[17]].…”
Section: Resultsmentioning
confidence: 99%
“…An increase of this betaine/creatinine ratio over the first 7 days of life was repeatedly observed and accorded to a higher total excretion of betaine [26][27][28][29][30]. Davies et al [26] reported a significant increase of the urine betaine/creatinine ratio in this time period.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports on this topic have been published (1)(2)(3)(4)(5). Several inborn errors in the pyrimidine metabolism are known.…”
mentioning
confidence: 99%